Cannabinoid Receptor 1 Expression in Human Dorsal Root Ganglia and CB13-Induced Bidirectional Modulation of Sensory Neuron Activity - Ford, Zachary K.; Reker, Ashlie N.; Chen, Sisi; Kadakia, Feni; Bunk, Alexander; Davidson, Steve (Frontiers in Pain Research, 2021)
Cannabinoid receptors have been identified as potential targets for analgesia from studies on animal physiology and behavior, and from human clinical trials. Here, we sought to improve translational understanding of the mechanisms of cannabinoid-mediated peripheral analgesia. Human lumbar dorsal root ganglia were rapidly recovered from organ donors to perform physiological and anatomical investigations into the potential for cannabinoids to mediate analgesia at the level of the peripheral nervous system. Anatomical characterization of in situ gene expression and immunoreactivity showed that 61% and 53% of human sensory neurons express the CB1 gene and receptor, respectively. Calcium influx evoked by the algogen capsaicin was measured by Fura-2AM in dissociated human sensory neurons pre-exposed to the inflammatory mediator prostaglandin E2 (PGE2) alone or together with CB13 (1uM), a cannabinoid agonist with limited blood-brain-barrier permeability. Both a higher proportion of neurons and a greater magnitude of response to capsaicin was observed after exposure to CB13, indicating cannabinoid-mediated sensitization. In contrast, membrane properties measured by patch-clamp electrophysiology demonstrated that CB13 suppressed excitability and reduced action potential discharge in PGE2 pre-incubated sensory neurons, suggesting suppression of sensitization. This bidirectional modulation of sensory neuron activity suggests that cannabinoids may suppress overall membrane excitability while simultaneously enhancing responsivity to TRPV1-mediated stimuli. We conclude that peripherally restricted cannabinoids may have both pro and anti-nociceptive effects in human sensory neurons.